Examining associations between suicidal desire, implicit fearlessness about death, and lifetime frequency of suicide attempts. Issue 6 (28th July 2022) - Tull, Matthew T.; DeMoss, Zachary T.; Anestis, Michael D.; Lavender, Jason M.; McDermott, Michael J.; Gratz, Kim L.
Abstract: Introduction: Suicide models propose that the capability for suicide, such as fearlessness about death (FAD), is necessary for the transition from suicidal desire to a suicide attempt. Most studies have relied on self‐report methods to assess FAD. However, this research has produced equivocal results. As individuals may have limited awareness of learned or pre‐existing associations between fearlessness and death, implicit measures of FAD hold promise. This study used a novel implicit association test (IAT), the IAT‐FAD, to examine associations between suicidal desire, implicit FAD, and lifetime suicide attempt frequency. Methods: Patients in residential substance use treatment ( N  = 75), a population with increased suicide risk and exposure to painful and provocative events, completed the IAT‐FAD and assessments of suicidal desire and past suicide attempts. Results: Implicit FAD moderated the association between suicidal desire and lifetime frequency of suicide attempts associated with an intent to die and requiring medical attention (although not ambivalent suicide attempts). Suicidal desire related to medically attended suicide attempts only at high implicit FAD levels, and to suicide attempts with a clear intent to die only at high or mean implicit FAD levels. Conclusion: Results provide initial support for the relevance of implicit measures of FAD for understanding suicide risk.